2000
DOI: 10.2337/diacare.23.12.1835
|View full text |Cite
|
Sign up to set email alerts
|

Association between C-reactive protein and features of the metabolic syndrome: a population-based study.

Abstract: OBJECTIVE -To assess the association of circulating levels of C-reactive protein, a sensitive systemic marker of inflammation, with different components of the metabolic syndrome.RESEARCH DESIGN AND METHODS -Total cholesterol (TC), HDL cholesterol, triglycerides, uric acid, BMI , and prevalence of diabetes and hypertension were assessed in 747 men and 956 women aged 18-89 years who were participating in the population-based National Health and Nutrition Survey, which was carried out in former West Germany in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

50
347
4
14

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 596 publications
(415 citation statements)
references
References 45 publications
50
347
4
14
Order By: Relevance
“…35 In type 2 diabetes, IL-6 levels are higher than in age-matched controls, 23 and a study of aboriginal men and women showed IL-6 to be an independent predictor of CRP levels. 26 In accordance with several studies, we found close associations between CRP, SAA and IL-6. Following surgery, the changes in SAA and IL-6 tended to parallel the changes in CRP, but were of lesser magnitude.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…35 In type 2 diabetes, IL-6 levels are higher than in age-matched controls, 23 and a study of aboriginal men and women showed IL-6 to be an independent predictor of CRP levels. 26 In accordance with several studies, we found close associations between CRP, SAA and IL-6. Following surgery, the changes in SAA and IL-6 tended to parallel the changes in CRP, but were of lesser magnitude.…”
Section: Discussionsupporting
confidence: 93%
“…[23][24][25] In a recent study of the polycystic ovary syndrome, obesity was reported to be the major determinant in driving the production of markers CRP, IL-6, and tumour necrosis factor. 9 Others found that CRP, in addition to BMI, 26 also correlated with the metabolic syndrome as indicated by insulin resistance, obesity, hypertension, impaired glucose tolerance, low HDL-cholesterol and hypertriglyceridaemia. 26 Similarly, the risk of developing type 2 diabetes in lean and overweight women could be explained by the strong correlation between CRP and fasting hyperinsulinaemia, 27 as CRP correlated independently with insulin sensitivity in healthy non-diabetic subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the correlation between large artery stiffness and CRP, other factors independently influence these markers. [21][22][23][24] New biomarkers are closely linked to the pathological mechanisms that underly the progression of atherosclerotic disease which ultimately precipitate acute clinical events. Current concepts of atherogenesis include involvement of the immune system and chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been shown that a chronic low inflammatory state, reflected by increased levels of C reactive protein (CRP) or other cytokines, is associated not only with atherosclerosis and cardiovascular disease [14,15], but also with the presence of the metabolic syndrome [16,17]. Noteworthy, the aging process itself is associated with both an increase in the plasma concentration of several pro-inflammatory cytokines [18], and a progressive decrease in plasma HDL-C concentration [19]; nevertheless, the possible co-occurrence of these two phenomena in older age has never been exhaustively investigated in population-based epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%